Reminders of behavioral disinhibition increase public conformity in the Asch paradigm and behavioral affiliation with ingroup members - Bos, Kees van den; Lind, E. A.; Bommelé, Jeroen; VandeVondele, Sebastian D. J. (Frontiers in Psychology, 2015)
This paper argues that being in the Asch situation, where there is a felt need to conform to others' faulty behaviors, poses a social threat to people. Furthermore, participating in a psychology experiment in which you will have to interact with other participants might trigger sense-making processes. The paper proposes that these assumed threats or sense-making processes are likely to activate the behavioral inhibition system, making people respond in more inhibited ways than they normally would be inclined to do. As a result, people's tendency to affiliate behaviorally with persons who are similar to them can be inhibited. The implication is that lowering behavioral inhibition (by experimentally reminding people about having acted without behavioral inhibitions) should lead to more public conformity in the Asch situation and stronger behavioral affiliation with ingroup members than not being reminded about behavioral disinhibition. Findings of four experiments support this line of reasoning. These findings are discussed in terms of behavioral inhibition and behavioral affiliation. Alternative accounts of the data that focus on social belongingness threats and optimal distinctiveness are also considered.